2018
DOI: 10.5603/pjnns.a2019.0002
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and TIA mimics in patients referred to a neurological emergency department by non-ambulance physicians, ambulance physicians and paramedics.

Abstract: Introduction. Our aim was to compare the structure and management of conditions mimicking acute cerebrovascular events (ACE) defined as stroke or transient ischaemic attack between patients referred directly to a neurological emergency department (ED) by non-ambulance physicians, ambulance physicians and paramedics. Methods. This is a retrospective study of 802 consecutive patients referred to a Polish urban neurological ED with a prehospital suspicion of ACE between January and December 2014. Results. After p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Nonetheless, the wide confidence intervals suggest that the proportion of correctly identified stroke cases vary greatly between different healthcare systems. For example, two studies in neighbouring Poland, a country with a similar primary care system, showed a resembling PPV and stroke mimic pattern [ 7 , 28 ]. One reason behind the difference in PPV between EMS and outpatient physicians could be a striking number of peripheral vestibulopathies being referred to the ED as stroke mimics by the outpatient physicians (18.0% vs. 0.9% of all stroke mimics, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the wide confidence intervals suggest that the proportion of correctly identified stroke cases vary greatly between different healthcare systems. For example, two studies in neighbouring Poland, a country with a similar primary care system, showed a resembling PPV and stroke mimic pattern [ 7 , 28 ]. One reason behind the difference in PPV between EMS and outpatient physicians could be a striking number of peripheral vestibulopathies being referred to the ED as stroke mimics by the outpatient physicians (18.0% vs. 0.9% of all stroke mimics, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of physicians in the ambulance seems to marginally improve the rates of diagnosis of ischaemic stroke. In a study from Poland with 805 patients referred to a neurological hospital, the rates of diagnosis of mimics were 35% for an ambulance with no physicians and 22% with ambulances with physicians [ 36 ]. Activation of “STARS” air transport via helicopter also experienced high rates of stroke mimics being transferred to the stroke centres.…”
Section: Assessment Of the Patient With Suspected Acute Strokementioning
confidence: 99%
“…Research shows an incorrect diagnosis in 66.3%. Incorrect diagnoses are mainly made in the pre-hospital setting, but can also happen in the ED, especially if the treating physician is not a neurologist or stroke physician [4]. The clinical hallmark is debilitating postural headache, exacerbated by standing, and relieved in the recumbent position.…”
Section: To the Editorsmentioning
confidence: 99%